2020
DOI: 10.1177/0218492320955062
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplastic left heart syndrome with anomalous origin of right pulmonary artery

Abstract: Classic hypoplastic left heart syndrome is a rare but fatal congenital heart disease associated with variable underdevelopment of the left side of the heart. Complex forms of hypoplastic left heart syndrome have been reported to coexist with anomalous pulmonary venous drainage, transposition of the great arteries, or pulmonary valve dysplasia. We report a case of hypoplastic left heart syndrome with anomalous origin of the right pulmonary artery from the ascending aorta a rare association not reported in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…4 It was reported that complex forms of HLHS coexist with anomalous pulmonary artery or pulmonary valve dysplasia. 5,6 If left untreated, the course of HLHS is inexorably progressive and ultimately fatal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It was reported that complex forms of HLHS coexist with anomalous pulmonary artery or pulmonary valve dysplasia. 5,6 If left untreated, the course of HLHS is inexorably progressive and ultimately fatal.…”
Section: Introductionmentioning
confidence: 99%
“…Circulation defects in HLHS lead to the enlargement of the right atrium, right ventricle, and pulmonary artery, as well as the patency of ductus arteriosus and foramen ovale 4 . It was reported that complex forms of HLHS coexist with anomalous pulmonary artery or pulmonary valve dysplasia 5,6 . If left untreated, the course of HLHS is inexorably progressive and ultimately fatal.…”
Section: Introductionmentioning
confidence: 99%